River waste to goldmine: A tale of floating agriculture in vulnerable southern regions of Bangladesh - Sarker, Mou Rani; Kundu, Nanda Dulal; Sujan, Md. Hayder Khan; Salman, Md; McKenzie, Andrew M.; Islam, Md. Monjurul; Rahman, Md. Alimur; Uddin, Md. Taj; Bhandari, Humnath; Sarkar, Md. Abdur Rouf (2025)
Floating agriculture transforms marshy lands into productive resources, enhancing food security and rural incomes in climate-vulnerable areas. While prior research highlights its potential as a climate-resilient practice, gaps remain in understanding the determinants of adoption and long-term livelihood impacts. Our study addresses these gaps by examining farming procedures, profitability, impacts, and the key drivers and challenges influencing floating agriculture adoption in southern Bangladesh. Data was collected from 158 farmers using a pre-tested questionnaire between October 2018 and April 2019. Profit function and logit regression models were applied to analyze profitability and socio-economic determinants, complemented by qualitative methods and causal loop diagrams to assess impacts. Findings reveal that farmers employ both intercropping and monocropping, with a preference for seedling raising (156.37 USD/100 m2) over vegetable cultivation (121.56 USD/100 m2) due to higher profitability. Despite its labor-intensive nature (73% labor costs for seedling rising vs. 85% for vegetable cultivation), floating agriculture boosts household income, meets local vegetable demand, and reduces reliance on external markets during shocks. Additionally, it provides ecological benefits such as waterweed management and reduced environmental pollution. Floating agriculture also alleviates poverty by enhancing agricultural production and generating a positive feedback loop of increased income, food availability, and improved nutrition and health. Adoption is influenced by age, experience, family size, income diversity, credit access, extension services, and market proximity. However, high capital costs, limited credit, market volatility, and biotic/abiotic stresses pose challenges. To scale up floating agriculture, policy measures should focus on financial support, technical training, cost-effective innovations, and fostering cooperative farming. Institutional backing is crucial for promoting this sustainable cleaner production practice in flood-prone regions of Bangladesh and similar global contexts.